On motions in a small neighborhood of zero of a multidimensional system - Nikitina, N.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The qualitative analysis of singular points of multidimensional systems is given. In three-dimensional systems (base models) that form attractors, the special points at zero can be saddle-headed or septofocus. In the bundle of two oscillators (Duffing and Van der Pol), the sum of characteristic indices at a singular point with syn ch ro nization is zero.